Cryptic coral reef microhabitats and the functional role of brittle stars in biogenic sediment generation - D. M. de Bakker; C. T. Perry; L. de Nooijer; A. J. Ramírez-Menéndez; J. E. Lloyd Newman; F. Hale; L. Alvarez-Filip (Coral Reefs, 2026)
Recent studies have highlighted the ecological importance of cryptic habitat space on coral reefs. These microhabitats, ranging from framework cavities to intra-branch space within marine macroalgae, can harbour diverse and ecologically relevant taxa. Here we show that brittle stars, ubiquitous across such cryptic habitats (reported densities exceeding 100 ind. m −2 ), represent an important, but previously neglected, source of skeletal sediment on reefs. Reef-derived carbonate sediment is generated by a range of reef biota and represents a critical geo-ecological process, contributing to reef structural development and vertical accretion via framework infilling, and the development and maintenance of lagoonal and shoreline habitats. Our sediment production estimates are based on skeletal carbonate content data for differently sized specimens of common brittle star morphotypes, combined with field-based density assessments from widespread microhabitat types (framework cavities, sub-rubble space and intra-algal skeletal branches) on Mexican Caribbean reefs. Resulting estimates suggest that brittle stars can make substantial contributions to reef sediment production (averaging 110 g m⁻ 2 yr⁻ 1 ; 95% CI 59–161). Spine-bearing taxa contribute disproportionately due to their high skeletal mass (> 6 g in large individuals) and high abundance (accounting for over 80% of sub-rubble populations). Resultant biogenic sediments are high-Mg calcite (15.6 ± 0.1 mol% MgCO₃) and predominantly disarticulate into fine to coarse-grained sand material (125 µm–2 mm). These findings highlight the underappreciated role of brittle stars in reef carbonate cycling. With many reef systems undergoing rapid changes in benthic ecology and microhabitat space availability, identifying and characterising links to biogenic sediment sources is central to understanding future reef sediment production regimes.